WEB MODUL IPA BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN THINKING SKILL - Agnesi Sekarsari Putri; Nurfina Aznam (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
SCIENCE WEB MODULE BASED ON GUIDED INQUIRY TO IMPROVE THINKING SKILLAbstractThe science web module is a systematically structured teaching material to achieve electronic learning objectives using website applications in which writing, animation, video, and navigation are exciting, interactive, active, and motivating learning that can facilitate students' thinking skills. Guided inquiry is a model that trains students to be actively involved in investigations with questions raised by teachers to direct students to find concepts. Guided inquiry-based web modules are used to improve students' thinking skills measured through written tests. This study uses a pretest-posttest control group design. Based on the results of the analysis using the Kruskal Wallis test, there are differences in the experimental class using the science web module based on guided inquiry and the control class using the science teaching materials commonly used by teachers. The results showed an increase in higher thinking skills in the experimental class than in the control class, resulting in the high effect size category so that the experimental class increased the thinking skills more effectively than the control class. AbstrakWeb modul IPA merupakan bahan ajar yang disusun sistematis untuk mencapai tujuan pembelajaran berbentuk elektronik menggunakan aplikasi website yang didalamnya terdapat tulisan, animasi, video, serta navigasi yang menjadi pembelajaran yang menarik, interaktif, aktif, dan memotivasi belajar yang dapat memfasilitasi thinking skill peserta didik. Inkuiri terbimbing merupakan model yang melatih peserta didik terlibat aktif dalam penyelidikan dengan pertanyaan-pertanyaan yang diajukan guru untuk mengarahkan peserta didik menemukan konsep. Web modul berbasos inkuiri terbimbing digunakan untuk meningkatkan thinking skill peserta didik. Penelitian ini menggunakan pretest posttest control group design. Thinking skill diukur melalui tes tertulis. Berdasarkan hasil analisis menggunakan uji Kruskal Wallis terdapat perbedaan kelas eksperimen yang menggunakan web modul IPA berbasis inkuiri terbimbing dengan kelas kontrol yang menggunakan bahan ajar IPA yang biasa digunakan guru. Hasil penelitian menunjukkan bahwa terdapat peningkatan thinking skill yang lebih tinggi pada kelas eksperimen daripada kelas kontrol, dengan hasil effect size kategori tinggi, sehingga kelas eksperimen meningkatkan thinking skill yang lebih efektif daripada kelas kontrol.